Răspuns :
a+b=91
b=[tex] \frac{75}{100}*a= \frac{3}{4}*a [/tex]
a+[tex] \frac{3a}{4}=91 [/tex] (aducem la acelasi numitor)
[tex] \frac{4a}{4}+ \frac{3a}{4}=91 [/tex]
[tex] \frac{7a}{4}=91 =\ \textgreater \ 7a=91*4=364 a=364:7 a=52[/tex]
a+b+91
52+b=91
b=91-52
b=39
b=[tex] \frac{75}{100}*a= \frac{3}{4}*a [/tex]
a+[tex] \frac{3a}{4}=91 [/tex] (aducem la acelasi numitor)
[tex] \frac{4a}{4}+ \frac{3a}{4}=91 [/tex]
[tex] \frac{7a}{4}=91 =\ \textgreater \ 7a=91*4=364 a=364:7 a=52[/tex]
a+b+91
52+b=91
b=91-52
b=39
a si b
a+b=91
b=75/100 * a => b=3/4 a =? 4b=3a
3a+3b=273
7b=273
b=39=> a=91-39 => a=52
a+b=91
b=75/100 * a => b=3/4 a =? 4b=3a
3a+3b=273
7b=273
b=39=> a=91-39 => a=52